2011
DOI: 10.1177/0748233711401263
|View full text |Cite
|
Sign up to set email alerts
|

Subacute effect of cigarette smoke exposure in rats

Abstract: This study was carried out to determine the preventive effect of Calendula officinalis L. (pot marigold) on rats exposed to cigarette smoke (CS). Rats were divided into three groups as control, CS and CS + pot marigold (PM). The rats in the CS and CS + PM groups were subjected to CS for 1 h twice a day for 23 days. PM (100 mg/kg body weight) was given to rats in the CS + PM group by gavage, 1 h before each administration period. While malondialdehyde, protein carbonyl contents and reduced glutathione level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…[ 10 ] The effects of many medicinal plants in UC have been investigated in the past decades. These include Strawberry,[ 11 ] Vitex negund ,[ 12 ] licorice,[ 13 14 ] Ginkgo biloba ,[ 15 ] Oroxylum indicu ,[ 1 ] Origanum onites ,[ 16 ] and Calendula officinalis [ 17 18 ] in rats, Polygonum multiflorum in mice,[ 19 ] Fragaria vesca [ 20 ] and Moringa olifera in albino rats,[ 12 ] Teucrium polium [ 21 ] and Calendula Officinalis in dog,[ 22 ] and C. officinalis in mice. [ 23 ]…”
mentioning
confidence: 99%
“…[ 10 ] The effects of many medicinal plants in UC have been investigated in the past decades. These include Strawberry,[ 11 ] Vitex negund ,[ 12 ] licorice,[ 13 14 ] Ginkgo biloba ,[ 15 ] Oroxylum indicu ,[ 1 ] Origanum onites ,[ 16 ] and Calendula officinalis [ 17 18 ] in rats, Polygonum multiflorum in mice,[ 19 ] Fragaria vesca [ 20 ] and Moringa olifera in albino rats,[ 12 ] Teucrium polium [ 21 ] and Calendula Officinalis in dog,[ 22 ] and C. officinalis in mice. [ 23 ]…”
mentioning
confidence: 99%
“…More similar to Fonte's study was Kaur's et al research, at which they verified the efficacy of the ethanol extract 95% of calendula flowers after the using of arginine in rats, for the reason that the arginine increases the standards of the mediatory inflammatory and índuces the metabolic acidosis, causing the necrotic pancreatitis [20] . Based on antioxidant, anti-inflammatory and healing of Calendula officinalis, which can be supported through the study by Okzol et al where it was showed that the calendula reduced aminotransferase aspartate, dehydrogenase lactate and phosphokinase creatine, oxidative stress in rats exposed to the cigarette fume and increased the HDL cholesterol rates [21] . The present research supported its results at which calendula extract reduced the levels of serum lipase at the third and fourteenth day, beyond that, it assuaged TBARS (levels of reative substances to the thiobarbituric acid) like index of lipids [22] and increased the levels of reduced GHS [20] .…”
Section: International Journal Of Advanced Engineering Research and Science (Ijaers)mentioning
confidence: 83%
“…Research has shown that C. officinalis contains flavonoids, polyphenols, lutein, flavoxanthin, lycopene, auroxanthin, beta-carotene which possesses antioxidant property[ 14 ] and hence can be utilized in the treatment of leukoplakia. In the light of above properties of C. officinalis , this study was proposed to assess the effect of herbal gel in treatment of homogeneous leukoplakia.…”
Section: Introductionmentioning
confidence: 99%